2015
DOI: 10.7185/geochemlet.1501
|View full text |Cite
|
Sign up to set email alerts
|

Preserved macroscopic polymeric sheets of shell-binding protein in the Middle Miocene (8 to 18 Ma) gastropod Ecphora

Abstract: Geochemical Perspectives Letters Letter Letter Geochemical Perspectives Letters gastropods that lived from the late Oligocene to the Pliocene (Carter et al., 1994; Ward and Andrews, 2008). Ecphora in its various species and subspecies span nearly 10 Ma of time along Calvert Cliffs, Maryland within the Calvert, Choptank and St. Marys Formations. This genus is unique in the context of the Calvert Cliffs fauna, in that pronounced colouration is preserved in the sculpted calcitic (CaCO 3) outer shell layer, as opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
3
2
Order By: Relevance
“…However, although proteinaceous material has been reported from shells of the Miocene gastropod Ecphora (Nance et al . 2015), in the present work, no indications were found that the polyenes of the cerithioidean gastropods could be bound to proteins. Nevertheless, it has to be considered that the actual colour of the polyene‐containing Miocene gastropods during lifetime may have been different to orange‐red, if they were bound to proteins.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…However, although proteinaceous material has been reported from shells of the Miocene gastropod Ecphora (Nance et al . 2015), in the present work, no indications were found that the polyenes of the cerithioidean gastropods could be bound to proteins. Nevertheless, it has to be considered that the actual colour of the polyene‐containing Miocene gastropods during lifetime may have been different to orange‐red, if they were bound to proteins.…”
Section: Discussioncontrasting
confidence: 65%
“…Putative carotenoproteins have been reported for the brachiopod Calloria from the Late Pleistocene of New Zealand (Curry 1999) and the gastropod Ecphora from the Middle Miocene of North America (Nance et al . 2015), but both studies mainly focused on the characterization of the proteinaceous material or the content of amino acids with very little information on the associated pigments. Otherwise, only hydrogenated carotenoids (non‐coloured carotanes) have been reported from fossil organisms, such as β ‐carotane that was detected in Pseudofagus leaves from the Miocene of Clarkia, Idaho (Giannasi & Niklas 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Interaction of unmethylated polyenes (psittacofulvins) with the protein keratin have been reported too (Stradi et al, 2001). However, although proteinaceous material has been reported from shells of the Miocene gastropod Ecphora (Nance et al, 2015), in the present work, no indications were found that the polyenes of the cerithioidean gastropods could be bound to proteins. Nevertheless, it has to be considered that the actual colour of the polyene-containing Miocene gastropods during lifetime may have been different than orange-red, if they were bound to proteins.…”
Section: Discussioncontrasting
confidence: 58%
“…Raman spectroscopy has been used to search for carotenoid pigments in amber-preserved feathers, but distinctive carotenoidinformative bands (at 1530 and 1153 cm -1 ) have been only obtained for present-day, but not for fossil feathers (Thomas et al, 2014b). Putative carotenoproteins were reported for the brachiopod Calloria from the Late Pleistocene of New Zealand (Curry, 1999) and the gastropod Ecphora from the Middle Miocene of North America (Nance et al, 2015), but both studies mainly focused on the characterization of the proteinaceous material or the content of amino acids with very little information on the associated pigments. Otherwise, only hydrogenated carotenoids (non-coloured carotanes) have been reported from fossil organisms, such as β-carotane that was detected in Pseudofagus leaves from the Miocene of Clarkia, Idaho (Giannasi and Niklas, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…The examination of specimens older than 1 Ma for preserved proteins began as early as the 1950s with non-MS approaches, including immunology, amino acid analyses, and nonproteomic MS approaches such as pyrolysis gas chromatography mass spectrometry (PY-GC-MS) , and time-of-flight secondary ion mass spectrometry (TOF-SIMS) . However, although the molecular techniques used to detect original organic constituents in fossils (e.g., Raman spectroscopy, , Fourier transform infrared spectroscopy [FT-IR], , TOF-SIMS) have become increasingly sophisticated and have typically remained more accessible and inexpensive than MS, only MS approaches (and MS/MS in particular) have the ability to generate the peptide sequence information .…”
Section: The Beginning Of Deep Time Paleoproteomicsmentioning
confidence: 99%